Application of Transference Focused Psychotherapy in Borderline Personality Disorders - Ina Dewi Ardiyani; Azimatul Karimah (Jurnal Psikiatri Surabaya, 2021)
Borderline Personality Disorder (BPD) is a condition that is currently commonly found in daily psychiatric practice, and causes serious psychiatric disorders because it has an impact on the emergence of various other comorbid psychiatric disorders. The management of BPD is a challenge, because it is quite difficult and complex. Psychotherapy is an effective first-line therapy for BPD. Transference Focused Psychotherapy (TFP) is psychodynamic based psychotherapy that is specifically designed for BPD and is considered effective based on the specific psychopathology of BPD, namely the lack of identity integration. TFP focuses on the relationship between patient and therapist in sessions which have the aim of facilitating better behavioral control and increasing reflection and influencing regulation so as to produce identity integration that leads to a more coherent identity, better regulatory abilities, less self-destructive behavior. forming a more balanced and constant relationship, and increasing overall functioning.Keywords : Borderline Personality Disorder, Psychodynamic Psychotherapy, Transference Focused Psychotherapy.